Computer Simulation of Great Lakes-St. Lawrence Seaway Icebreaker Requirements. - Kotras, Thomas V; Peter, James J (1980)
A computer simulation was developed as a planning tool to aid in establishing future icebreaker requirements for the Great Lakes-St. Lawrence Seaway as a function of projected cargo tonnage, trade routes, winter severity, vessel ice transiting capabilities, vessel operating restrictions, and alternate icebreaking plans and operating concepts (direct assistance, convoying, and channel ice clearing). The simulation allows the user to determine benefits in terms of reduced commercial transit time, reduced shipping cost and increased fleet tonnage capacity; to assess the impact of user charges on shipping costs; and to investigate alternate fleet mixes of icebreakers and icebreaking tugs and their assigned areas of operation. The simulation has the following two operating modes: (1) a fixed fleet of icebreakers; and (2) maximum response time where the required icebreaker fleet is determined internally. In addition to describing the simulation, validation of the simulation is presented based on U.S. Coast Guard records for the 1975-76 winter navigation season, and the results, conclusions, and recommendations of ten (10) production runs performed to examine the effect on icebreaker requirements of: (1) 20% increase in cargo over the year 2000 projections; (2) convoys; (3) winter severity; (4) imposed vessel restrictions; (5) channel ice clearing; and (6) prohibiting icebreaking tugs from convoying. Based on these runs, a preliminary icebreaker fleet for the Great Lakes was generated to handle the projected cargo in the year 2000.